Major Determinants of Anemia in Pregnant Women Residing in the Urban Slums of Taluka Qasimabad, District Hyderabad (Medical Forum Monthly, 2024)
Objective: To find out major determinants of anemia in pregnant women residing in the urban slums of Taluka Qasimabad, district Hyderabad.Study Design: Cross-sectional descriptive study.Place and Duration of Study: This study was conducted in urban slum areas of Taluka Qasimabad, District Hyderabad during six months of study period i.e. from 1st March 2011 to 31st August 2011.Patients and Methods: The total population residing in the study areas was twelve thousand two hundred and seven. During the study period of six months, two hundred and fifty pregnant women were enrolled for the study. Pregnant women during 2nd and 3rd trimester of pregnancy were included in the study. The data was collected by conducting interviews, filling of the pre-tested, structured questionnaire and by assessing anemia by determining the hemoglobin level in the enrolled pregnant women. The questionnaire was a close-ended one, filled by the principle researcher herself. It comprised of demographic information about woman. Every woman’s hemoglobin was determined by using Sahli’s Hemoglobinometer. Anemia in pregnancy according to WHO classified into mild anemia hemoglobin level in the range of 10.0-10.9 g/dl, moderate anemia hemoglobin level in the range of 7-9.9 g/dl and severe anemia hemoglobin level is <7 g/dl.Results: The association of various factors (determinants) with anemia was analyzed by applying chi-squared test; the p-value of <0.05 was taken as the level of significance. Two hundred and thirty three pregnant women were anemic while only seventeen women (6.8%) were found non-anemic. Majority of the women i.e. 70% presented with moderate anemia (hemoglobin level 7.0-9.9Gm /dl) while severe anemia (hemoglobin level <7 Gm/dl) was recorded in 5.2% pregnant women. There was strong statistically significant association seen between parity of pregnant women and the degree/severity of anemia (p=0.00). There was strong association between socio-economic status and the severity of anemia (p=0.00). The family type was strongly associated with the severity of anemia (p=0.01).Conclusion: Prevalence and severity of anemia in pregnant women residing in urban slum areas of Taluka Qasimabad, District Hyderabad is high. Current findings highlight the anemia in pregnancy as a priority area of concern.